A Water Flow Control with OnLine Neurofuzzy Controller using a Dynamic Learning Rate - Gomes, Hugo; Ferreira, Carolina; Oliveira, Everthon; Reis, Agnaldo; Caminhas, Walmir (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e Computacional, 2018)
This paper describes an ONFC (OnLine Neurofuzzy Controller) application with a dynamic learning rate to control the water flow of a real plant. A revision of ONFC is presented and the ONFCDw version is used, which has an action that minimizes the increase in the difference between the controller weights. The dynamic learning rate used to update the controller weights is described and the results of experiments performed in a water flow control process are presented, comparing the results with the PID controller used in the process.